2009
DOI: 10.1177/1933719108329818
|View full text |Cite
|
Sign up to set email alerts
|

Placenta-derived Chymotrypsin-like Protease (CLP) Disturbs Endothelial Junctional Structure in Preeclampsia

Abstract: Placenta-derived chymotrypsin-like protease may contribute to endothelial activation in preeclampsia. In this study, we determined if placenta-derived chymotrypsin-like protease could disturb endothelial junctional integrity to promote endothelial permeability in preeclampsia. Confluent endothelial cells were cocultured with placental trophoblasts or treated with preeclampsia placenta-conditioned medium. Endothelial junction protein vascular endothelial cadherin expression and distribution were examined by flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…We also found that CLP produced by preeclamptic placentas is a likely mediator that produces this harmful effect against endothelial cells (4). However, the mechanism by which CLP induced endothelial barrier dysfunction is largely unknown.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…We also found that CLP produced by preeclamptic placentas is a likely mediator that produces this harmful effect against endothelial cells (4). However, the mechanism by which CLP induced endothelial barrier dysfunction is largely unknown.…”
Section: Discussionmentioning
confidence: 74%
“…We previously reported that placental-derived CLP is a likely candidate to induce endothelial activation and VE-cadherin disorganization at cell junctions (4,15). To find out if placental-derived CLP could activate PAR-2 in endothelial cells, chymotrypsin was depleted from the placental conditioned medium and then conditioned medium with or without chymotrypsin depletion were used to treat endothelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the innate immune activities of the digestive system and a strong resemblance between human intestinal epithelia and fish epithelia, it is reasonable to expect digestion genes to play a role in the immune response in fish skin. For example, CTRL (Chymotrypsin-like protease) has been shown to induce endothelial activation, a pro-inflammatory and pro-coagulant state of the endothelial cells, in humans (Gu et al, 2009). Although the function of ACE2 is not clear, it has been shown to be involved in the response to viral infection (Donoghue et al, 2000; Tipnis et al, 2000).…”
Section: Resultsmentioning
confidence: 99%